2004
DOI: 10.1080/09603120410001725630
|View full text |Cite
|
Sign up to set email alerts
|

Hospital waste management status in university hospitals of the Fars province, Iran

Abstract: Hospital waste contains large quantities of hazardous materials. In Iran, as in many developing countries, not much attention has been paid to this matter. Little information is available regarding the generation and disposal of medical waste in Iran, and this fact hinders planning for a better management of the aforementioned waste. This paper describes a survey performed on the collection and disposal of waste in the university hospitals of the Fars province, which are the medical referral centres in the sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 3 publications
5
37
1
2
Order By: Relevance
“…This seemingly poor usage of PPEs among sanitation staffs was also found among sanitation staff of in the study in Rawalpindi, Pakistan 29 and also lack of knowledge of use of PPEs in the study at the Fars University, hospital in Iran. 24 Average waste generation per bed was 2.40kg/bed/day and this was similar to what was obtained in the FCT, Abuja, Nigeria where it was stated to 2.78kg/bed/day. 18 Lower values have been reported from Lagos, 19 Ilorin, 20 and Irrua, 16 However, per capital waste generation was much higher in Iran and the United States where it was 4.45kg and 6.93kg/bed/day respectively.…”
Section: International Journal Of Environment Agriculture and Biotecsupporting
confidence: 67%
See 4 more Smart Citations
“…This seemingly poor usage of PPEs among sanitation staffs was also found among sanitation staff of in the study in Rawalpindi, Pakistan 29 and also lack of knowledge of use of PPEs in the study at the Fars University, hospital in Iran. 24 Average waste generation per bed was 2.40kg/bed/day and this was similar to what was obtained in the FCT, Abuja, Nigeria where it was stated to 2.78kg/bed/day. 18 Lower values have been reported from Lagos, 19 Ilorin, 20 and Irrua, 16 However, per capital waste generation was much higher in Iran and the United States where it was 4.45kg and 6.93kg/bed/day respectively.…”
Section: International Journal Of Environment Agriculture and Biotecsupporting
confidence: 67%
“…22 In this study, only 43.3% of the respondents practiced waste segregation by disposing waste into colour coded plastic bags or containers, while 58.8% of the respondents deposit both medical and non-medical waste into same plastic or containers. Segregation of medical waste from non-medical waste was almost completely lacking in this study except from segregation of sharps, and this is in keeping with several studies like the study in two general hospitals in Lagos, Nigeria, 3 Another study in the Federal Capital Territory (FCT), Nigeria 18 ; studies in the Fars Province of Iran 23 and the University Hospital in Fars, Iran 24 ; other studies in Jos 25 and PortHarcourt, 26 Nigeria, that all reported poor segregation of medical from general wastes. Contrary to findings in this study, are reports of high priority segregation of infectious medical waste from general waste as reported in studies done in Lagos, Nigeria in two private and two public hospitals with bed capacity of 40 to 600 beds.…”
Section: International Journal Of Environment Agriculture and Biotecsupporting
confidence: 65%
See 3 more Smart Citations